Genetic, antigenic and phenotypic comparison of herpesviruses isolated from domestic and wild felids - Venter, Estelle Hildegard (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2009.